2023
DOI: 10.1088/1755-1315/1169/1/012090
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating consumer preferences based on the total antioxidant activity of the Indonesian herbal drink “Bandrek”

Abstract: Traditional herbal drink is made from local herbs and is believed to be able to increase immune system. Bandrek is a Javanese traditional drink commonly made with local herbs and spices. One of the important ingredients should be added in bandrek is ginger. The objective of this study is to investigate consumers’ preferences of bandrek with different processing treatments of ginger (control, cold press, oven-cold press, cold press-boiled, smashed-boiled). In addition, sensorial profiles of bandrek with differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…According to Fitriarni et al (2021), mixing spice drinks with fruit would help improve the sensory properties of the drinks to be more accepted by consumers of all ages or for those who do not even like the unpleasant smell of spices. Similarly, Wilianto and Ervina (2023), who evaluated the sensory of bandrek, revealed that panelists tended to like the sample with low intensity of bitter aftertaste. It contributed to consumers' liking because the bitter taste does not overpower the drink's taste and is still covered by other aromatic sensory attributes, such as the sweet taste of sugar.…”
Section: Component 4: Product Sensorymentioning
confidence: 96%
See 1 more Smart Citation
“…According to Fitriarni et al (2021), mixing spice drinks with fruit would help improve the sensory properties of the drinks to be more accepted by consumers of all ages or for those who do not even like the unpleasant smell of spices. Similarly, Wilianto and Ervina (2023), who evaluated the sensory of bandrek, revealed that panelists tended to like the sample with low intensity of bitter aftertaste. It contributed to consumers' liking because the bitter taste does not overpower the drink's taste and is still covered by other aromatic sensory attributes, such as the sweet taste of sugar.…”
Section: Component 4: Product Sensorymentioning
confidence: 96%
“…The Kansei word bitter had the lowest loading factor of 0.390, indicating a weak factor and must be excluded from component 4 (Rahardjo, 2013). The bitter aftertaste is undesirable and may promote dislike (Wilianto & Ervina, 2023). The bitter aftertaste is closely associated with the ginger aftertaste or hot sensation of spice drinks (Sarkar & Alam, 2018).…”
Section: Component 4: Product Sensorymentioning
confidence: 99%
“…6, No. 2 (2024) 116-122 120 [22]. These compounds contribute to the flavor profile of the beverage while offering potential therapeutic effects.…”
Section: First Author Et Almentioning
confidence: 99%